The strong gravitationally lensed Herschel galaxy HLock01: Optical spectroscopy reveals a close galaxy merger with evidence of inflowing gas - Marques-Chaves, R; Pérez-Fournon, I; Gavazzi, R; Martínez-Navajas, P; Riechers, D; Rigopoulou, D; Cabrera-Lavers, A; Clements, D; Cooray, A; Farrah, D; Ivison, R; Jiménez-Ángel, C; et al. (Institute of Physics, 2018)
The submillimeter galaxy (SMG) HERMES J105751.1+573027 (hereafter HLock01) at z =2.9574 ±0.0001 is one of the brightest gravitationally lensed sources discovered in the Herschel Multi-tiered Extragalactic Survey. Apart from the high flux densities in the far-infrared, it is also extremely bright in the rest-frame ultraviolet (UV), with a total apparent magnitude mUV≃ 19.7 mag. We report here deep spectroscopic observations with the Gran Telescopio Canarias of the optically bright lensed images of HLock01. Our results suggest that HLock01 is a merger system composed of the Herschel-selected SMG and an optically bright Lyman break-like galaxy (LBG), separated by only 3.3 kpc in projection. While the SMG appears very massive (M∗≃ 5 ×1011Mo), with a highly extinguished stellar component (AV≃ 4.3), the LBG is a young, lower-mass (M∗≃ 1 ×1010Mo), but still luminous (10 × LUV∗) satellite galaxy. Detailed analysis of the high signal-to-noise ratio (S/N) rest-frame UV spectrum of the LBG shows complex kinematics of the gas, exhibiting both blueshifted and redshifted absorption components. While the blueshifted component is associated with strong galactic outflows from the massive stars in the LBG, as is common in most star-forming galaxies, the redshifted component may be associated with gas inflow seen along a favorable sightline to the LBG. We also find evidence of an extended gas reservoir around HLock01 at an impact parameter of 110 kpc, through the detection of C ii λλ1334 absorption in the red wing of a bright Lyα emitter at z ≃ 3.327. The data presented here highlight the power of gravitational lensing in high S/N studies to probe deeply into the physics of high-z star-forming galaxies.